Implementasi Nilai Nilai Kebangsaan Berbasis UUD 1945 Pada Analisis Strategi Pemasaran Digital Perusahaan dalam Meningkatkan Pelayanan Penjualan Migas di Indonesia - Edy Soesanto; Rafid Endika; Bagus Hery Refangga (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Indonesia has abundant natural resources, one of which is oil and gas. Oil and gas companies will also continue to increase productivity in line with the many demands from consumers. Several large companies in Indonesia, such as Pertamina, Shell, Total, Petronas, and most recently Vivo, are involved in the downstream fuel oil business competition. One of the things that can be improved by companies to overcome threats and challenges in market competition is to maintain the quality of the company itself. Services to consumers such as criticism and input can be available quickly through digital media intermediaries. The company uses digital strategies to improve oil and gas sales services. Of course, these facilities must involve the use of digital technology where the 1945 Constitution is the legal basis that regulates all aspects of the life of the Indonesian nation, ranging from human rights, governance, and citizen rights including technology and digitalization. Advances in information system technology have entered from various fields, so that the existence of the ITE Law has the aim of forming regulations in the field of information and communication technology in Indonesia. For the implementation of the ITE Law, it regulates how to use internet-based media so that accuracy and caution are needed in conducting digital marketing so that the electronic information published is feasible and appropriate and supports oil and gas sales services.